Competency Functional Profile of the University Teacher: Value Approach - I. A. Gazieva; A. A. Burashnikova (Высшее образование в России)
The article presents the result of developing the model of the competence profile of a teacher as the basis for the system of revealing, assessing and developing professional skills of a teacher, including competences, which have a significant impact on the quality of pedagogical and scientific work of a teacher. The emphasis is put on different levels of competence profile: functional (competencies necessary for teachers to develop and disseminate research, innovation, and educational practices) and value (competencies acquired and developed by a teacher under the influence of stimulating professional environment and values of corporate culture of professional community and HEI). The empirical basis of the article is the results of a series of focus groups and strategy sessions with teaching and administrative staff and students reflecting the peculiarities of perception of “professional mastery of a teacher” perception as a defining category of quality pedagogical process in higher education.